2013
DOI: 10.1128/aem.03850-12
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of the 2009 Pandemic Influenza A (H1N1) Virus on N95 Respirators

Abstract: times (4, 12, 24, 48, 72, and 144 h). pH1N1 was distributed onto N95 coupons (3.8 to 4.2 cm 2 ) and extracted by a vortex-centrifugation-filtration process, and the ability of the remaining virus to replicate was quantified using an enzyme-linked immunosorbent assay (ELISA) to determine the log 10 concentration of the infectious virus per coupon. Overall, pH1N1 remained infectious for 6 days, with an approximately 1-log 10 loss of virus concentrations over this time period. Time and AH both affected virus surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(72 citation statements)
references
References 27 publications
2
69
1
Order By: Relevance
“…5 Bacteriophage $ 6 was inactivated somewhat more rapidly than H1N1 influenza on N95 surfaces at 60% RH (possibly as a result of the matrix used), and a similar trend of greater inactivation was observed at higher humidity levels. 6 The results are similar to those found for transmissible gastroenteritis virus, a member of the coronavirus family, on respirator surfaces. 7 This suggests that bacteriophage $ 6 is a potential surrogate for studies of human respiratory viruses on personal protective equipment.…”
supporting
confidence: 80%
“…5 Bacteriophage $ 6 was inactivated somewhat more rapidly than H1N1 influenza on N95 surfaces at 60% RH (possibly as a result of the matrix used), and a similar trend of greater inactivation was observed at higher humidity levels. 6 The results are similar to those found for transmissible gastroenteritis virus, a member of the coronavirus family, on respirator surfaces. 7 This suggests that bacteriophage $ 6 is a potential surrogate for studies of human respiratory viruses on personal protective equipment.…”
supporting
confidence: 80%
“…For example, it has previously been demonstrated that there is an increased persistence of influenza A virus in the presence of mucus (25,26). However, in our study, the sample matrix (e.g., viral medium, FBS, mucin) did not influence influenza A virus persistence, which was also demonstrated by Coulliette et al (22). It is important to note that the source of mucus for all three studies was different and data are not available to explain how this may impact virus persistence.…”
Section: Discussioncontrasting
confidence: 47%
“…These combined parameters have not been previously investigated using a tissue culture-based ELISA. Although the two strains chosen for use in this study no longer circulate in humans, they act as a surrogate for the pandemic strain, which has been shown to have survival characteristics similar to those of the strains used in this study (22). Previous studies of virus persistence on environmental surfaces have found that various strains of influenza A (H1N1) virus remain infectious on stainless steel surfaces for approximately 24 h but no longer than 72 h (15)(16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some studies have tested more than one strain of influenza, highlighting considerable strain variation. 18,35,39,42 Further work is necessary to evaluate the importance of strain variation in influenza and coronavirus survival.…”
Section: Survival On Dry Surfacesmentioning
confidence: 99%